Exploring the exercise for enhancing postural control, gait, and muscle strength in older adults with diabetic peripheral neuropathy: a systematic review and meta-analysis - Pang, Xiangsheng; Wang, Dongmei; Zhang, Fei; Guo, Bin; Liu, Wenming (Frontiers in Aging, 2025)
ObjectiveThe purpose of this study was to conduct a systematic review and meta-analysis to evaluate the effects of exercise on postural control, gait, and muscle strength in older adults with diabetic peripheral neuropathy (DPN).Research DesignSystematic review and meta-analysis.MethodsAn extensive literature search was performed in PubMed, EBSCO, Web of Science and Cochrane Library from database inception to 30 September 2023. The inclusion criteria were exercise intervention on postural control, gait characteristics, and muscle strength in older adults with DPN. Two reviewers independently extracted data and assessed the quality of studies by Cochrane Risk of Bias.ResultsThe literature search elicited a total of 523 references, 23 articles were included in this systematic review and meta-analyses. Exercise could effectively decrease the Centre of Pressure (COP) path (SMD = −0.38, 95%CI = −0.77 ∼ 0.01), increase gait speed (MD = 0.08, 95%CI = 0.05 ∼ 0.11), but did not change stride length (MD = 0.04, 95%CI = −0.01 ∼ 0.09), and enhance muscle strength (SMD = 0.76, 95%CI = 0.19 ∼ 1.33).ConclusionExercise improves postural control, gait speed, and muscle strength in older adults with DPN, reducing fall risk and enhancing lower limb strength, though evidence on stride length improvement is limited.Systematic Review Registrationidentifier CRD42023436799.